Increased Levels of miRNA-146a in Serum and Histologic Samples of Patients with Uveal Melanoma - Russo, Andrea; Caltabiano, Rosario; Longo, Antonio; Avitabile, Teresio; Franco, Livio M.; Bonfiglio, Vincenza; Puzzo, Lidia; Reibaldi, Michele (Frontiers in Pharmacology, 2016)
Purpose: To analyze MiRs expression in serum of UM patients, respect to healthy donors, and to compare this data with MiRs expressed in formalin-fixed, paraffin-embedded UM samples. Methods: Expression profile of 754 miRNAs was performed in serum of patients with uveal melanoma who underwent primary enucleation. The level of miRNAs increased in serum was individually analyzed on FFPE UM samples and compared to choroidal melanocytes from unaffected eyes. Results: Fourteen patients with uveal melanoma were included in the study. We found 8 serum miRNAs differentially expressed compared to normal controls: 2 upregulated miRNAs (miRNA-146a, miR-523); 6 downregulated miRNAs (miR-19a, miR-30d, miR-127, miR-451, miR-518f, miR-1274B). When data on upregulated miRNAs were singularly validated only a significant overexpression of miRNA-146a was found. A statistically significant upregulation of miRNA-146a was also found on FFPE UM samples, compared to choroidal melanocytes from unaffected eyes. Conclusions: miRNA-146a is increased in serum of patients with UM and in FFPE tumor samples. Further studies will show if it could be considered a potential marker of UM in the blood.